A Policy Analysis of Reserve Retirement Reform - Asch, Beth J. (RAND Corporation, 2013)
As the defense burden borne by reserve forces has increased, more attention has been paid to differences between retirement systems for the reserve and active components. This report analyzes the systems, discusses the importance of structuring compensation to enable management flexibility, considers obstacles and how they might be overcome, and provides a quantitative assessment of the reserve retention and cost effects of possible proposals.